He ping yu zhan zheng : yi jiu san yi zhi yi jiu si yi nian jian Meiguo zhi wai jiao zheng ce (Pre-Kangzhan and Kangzhan Period Preservation Project, 1943)
Dept. of State White paper on United States foreign policy, 1931-1941, during peace and war.